Environmental Law: International Trends and National Characteristics - KUCHENIN, Evgeny Sergeevich; LOSHKAREV, Igor Olegovich; LUTOVINOVA, Natalya Viktorovna; LAVRENTIEVA, Maria Sergeyevna (Journal of Environmental Management and Tourism; Vol 10 No 7 (2019): JEMT Volume X Issue 7(39) Winter 2019, 2020)
Environmental law is an actively developing branch of law in all countries, including Russia. Changes in the sphere of legal regulation of environmental management, protection and safety as an element of national security, like in any other branch of law, are due to the need to constantly improve the legal regulation of social relations. However, changes in the field of environmental law are particularly dynamic. This is due to, on the one hand, the continuing growth of adverse effects on the environment and, on the other hand, the development of new resource and energy-saving technologies and the need for their more active implementation in economic activities, as well as the application of effective management procedures. The article suggests directions for the development of the environmental law branch management in the Russian legal system. First, the norms of environmental law are now becoming fundamental in terms of ensuring basic human rights and freedoms, primarily, the right to life and health protection. Second, the norms of environmental law must be aimed at ensuring the well-being of future generations. Third, it is the complex intersectoral nature of environmental law and, accordingly, the breadth and diversity of sources containing the norms of environmental law. Finally, it is the global nature of environmental problems and, accordingly, the need to coordinate the efforts of the international community in matters of legal regulation of environmental protection, as well as the international exchange of experience in this area and focus on the experience of countries that have achieved the most significant results in the development of environmental legislation.